N–nitrosamines are associated with shorter telomere length - Heng Li; Bo AG Jönsson; Christian H Lindh; Maria Albin; Karin Broberg (Scandinavian Journal of Work, Environment & Health, 2011)

(untitled)
OBJECTIVES: Telomeres are critical to maintain the integrity of the chromosomes, and telomere abnormalities are important features of carcinogenesis. Telomere length differs among individuals due to genetic and environmental factors. Aiming to examine the relationship between DNA-damaging agents and average telomere length in peripheral blood, we conducted a cross-sectional study among 157 workers working in the rubber industry in Sweden. METHODS: N-nitrosamines were measured in air by personal sampling on Thermosorb/N tubes and analyzed by liquid chromatography tandem mass spectrometry (LC/MS/MS) for 60 individuals. Based on a similar working situation, the exposure was estimated for all workers. Polycyclic aromatic hydrocarbons (PAH) were measured as the metabolite 1-hydroxypyrene (1-HP) in urine by LC. Carbon disulphide (CS2) was measured as the metabolite 2-thiothiazolidine-4-carboxylic acid (TTCA) in urine by LC/MS/MS. Toluidines (orto-, meta-, and para-) were measured in urine by gas chromatography (GC)/MS. The average telomere length in peripheral blood was determined by quantitative polymerase chain reaction (PCR). RESULTS: There was a reduction in telomere length with increasing exposure to N-nitrosamines in air [measured (N=60) N-nitrosamines β-coefficient= -10, (95% confidence interval [95% CI] -17– -1.9) P=0.016; estimated (N=157) N-nitrosamines β-coefficient = -5.3, (95% CI -9.5– -0.97) P=0.016]. Also, there were negative associations between para-toluidine [β-coefficient= -0.031 (95% CI -0.055– -0.0063) P=0.014], as well as age β-coefficient= -0.005 (95% CI -0.007– -0.002) P=0.001] and telomere length. There were no strong associations between other exposures and telomere length nor did smoking modify the effect. CONCLUSION: N-nitrosamines exposure may lead to telomere shortening.